Mesoporous CoxSn(1–x)O2 as an efficient oxygen evolution catalyst support for SPE water electrolyzer. Issue 4 (24th April 2019) - Chen, Gang; Li, Jiakun; Lv, Hong; Wang, Sen; Zuo, Jian; Zhu, Lihua
Abstract : SPE water electrolysis is a promising method of hydrogen production owing to its multiple strengths, including its high efficiency, high product purity and excellent adaptability. However, the overpotential of the oxygen evolution reaction process and consumption of Ir during charging in SPE water electrolysis will inevitably result in large energy loss and then high cost. Under these circumstances, we propose a novel 40IrO2 /Co x Sn(1− x ) O2 ( x = 0.1, 0.2, 0.3) anode catalyst, where the Co x Sn(1− x ) O2 support is synthesized by a hydrothermal method and IrO2 is synthesized by a modified Adams fusion method. After modifying the component of Co x Sn(1− x ) O2, the 40IrO2 /Co x Sn(1− x ) O2 exhibits an increased specific surface area, electrical conductivity and surface active sites. Moreover, a single cell is fabricated by Pt/C as cathode catalyst, 40IrO2 /Co x Sn(1− x ) O2 as anode catalyst and Nafion 117 membrane as electrolyte. The 40IrO2 /Co0.2 Sn0.8 O2 exhibits the lowest overpotential (1.748 V at 1000 mA cm −2 ), and only 0.18 mV h −1 of voltage increased for 100 h durability test at 1000 mA cm −2 . Consequently, Co x Sn(1− x ) O2 is a promising anode electrocatalyst support for an SPE water electrolyzer.